Click-designed vanilloid-triazole conjugates as dual inhibitors of AChE and Aβ aggregation. Issue 5 (19th January 2023) - Elsbaey, Marwa; Igarashi, Yasuhiro; Ibrahim, Mahmoud A. A.; Elattar, Eman
Abstract : Based on their reported neuroprotective properties, vanilloids provide a good starting point for the synthesis of anti-Alzheimer's disease agents. Abstract : Based on their reported neuroprotective properties, vanilloids provide a good starting point for the synthesis of anti-Alzheimer's disease (AD) agents. In this context, nine new 1, 2, 3-triazole conjugates of vanilloids were synthesized via click chemistry. The compounds were tested for their effect on acetylcholine esterase (AChE) and amyloid-beta peptide (Aβ) aggregation. The triazole esters ( E )-(1-(4-hydroxy-3-methoxybenzyl)-1 H -1, 2, 3-triazol-4-yl)methyl 3-(4-hydroxy-3 methoxyphenyl)acrylate 9 and (1-(4-hydroxy-3-methoxybenzyl)-1 H -1, 2, 3-triazol-4-yl)methyl-4-hydroxy-3-methoxybenzoate 8 displayed dual inhibitory activity for AChE and Aβ aggregation with IC50 values of 0.47/0.31 μM and 1.2/0.95 μM, respectively, as compared to donepezil (0.27 μM) and tacrine (0.41 μM), respectively. The results showed that the triazole ester moiety is more favorable for the activity than the triazole ether moiety. This could be attributed to the longer length of the spacer between the two vanillyl moieties in the triazole esters. Furthermore, the binding affinities and modes of the triazole esters 9 and 8 were examined against AChE and Aβ utilizing a combination of docking predictions and molecular dynamics (MD) simulations. Docking computations revealed promising binding affinity of triazole esters 9 and 8 as potential AChE, Aβ40, and Aβ42 inhibitors with docking scores of −10.4 and −9.4 kcal mol −1, −5.8 and −4.7 kcal mol −1, and −3.3 and −2.9 kcal mol −1, respectively. The stability and binding energies of triazole esters 9 and 8 complexed with AChE, Aβ40, and Aβ42 were measured and compared to donepezil and tacrine over 100 ns MD simulations. According to the estimated binding energies, compounds 9 and 8 displayed good binding affinities with AChE, Aβ42, and Aβ40 with average Δ G binding values of −32.9 and −31.8 kcal mol −1, −12.0 and −10.5 kcal mol −1, and −20.4 and −16.6 kcal mol −1, respectively. Post-MD analyses demonstrated high steadiness for compounds 9 and 8 with AChE and Aβ during the 100 ns MD course. This work suggests the triazole conjugate of vanilloids as a promising skeleton for developing multi-target potential AD therapeutics.